The efficacy of weekly and bi-weekly heat training to maintain the physiological benefits of heat acclimation. Issue 3 (March 2022) - Benjamin, Courteney L.; Sekiguchi, Yasuki; Armstrong, Lawrence E.; Manning, Ciara N.; Struder, Jeb F.; Butler, Cody R.; Huggins, Robert A.; Stearns, Rebecca L.; Lee, Elaine C.; Casa, Douglas J.
Abstract: Objectives: To examine the efficacy of weekly and bi-weekly heat training to maintain heat acclimatization (HAz) and heat acclimation (HA) for 8 weeks in aerobically trained athletes. Design: Randomized, between-group. Methods: Twenty-four males (mean [m ± standard deviation [sd]; (age, 34 ± 12 y; body mass, 72.6 ± 8.8 kg, VO2peak, 57.7 ± 6.8 mL·kg −1 ·min −1 ) completed five trials (baseline, following HAz, following HA (HAz + HA), four weeks into heat training [HTWK4 ], and eight weeks into HT [HTWK8 ] that involved 60 min of steady-state exercise (59.1 ± 1.8% vVO2peak ) in an environmental laboratory (wet bulb globe temperature [WBGT], 29.6 ± 1.4 °C) on a motorized treadmill. Throughout exercise, heart rate (HR) and rectal temperature (Trec ) were recorded. Following HAz + HA, participants were assigned to three groups: control group (HT0 ), once per week heat training (HT1 ), and twice per week heat training (HT2 ). HT involved heated exercise (WBGT, 33.3 ± 1.3 °C) to achieve hyperthermia (38.5–39.75 °C) for 60 min. Repeated measures ANOVAs were used to determine differences. Results: HAz + HA resulted in significant improvements in HR ( p < 0.001) and Trec ( p < 0.001). At HTWK8, HR was significantly higher in HT0 (174 ± 22 beats⋅min −1 ) compared to HT2 (151 ± 17 beats⋅min −1, p < 0.023), but was not different than HT1 (159 ± 17 beats⋅min −1, p = 0.112). There was no difference in % change of Trec from post-HAz + HA to HTWK4 (0.6 ± 1.3%; p = 0.218), however, HTWK8 (1.8 ± 1.4%) was significantly greater than post-HAz + HA in HT0 ( p = 0.009). Conclusions: Bi-weekly HT provided clear evidence for the ability to maintain physiological adaptions for 8 weeks following HA.